BIROKRASI DAN POTENSI KONFLIK DI INDONESIA - Sulistyaningsih, Endang (Jurnal Kebijakan Publik, 2010)
Conflict is often seen as a destructive event (destruktitif) and harm the public. In fact the conflictis a normal process in society other than the process of competition and consensus or harmony. In this casethe conflict is defined as “differences of opinion between two or more parties (groups)”. Conflicts can beaccompanied by violence (physical, war) or non-violence (“war of words”, “conflict law”). In this case theconflict can also be a purpose to destroy or defeat the opponent or as a way to reach the goal.